Analisis Dampak Rotasi Kerja Karyawan terhadap Kinerja Karyawan PT HK Realtindo - Selina, Inka; Palupi, Majang (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The purpose of this research to find out how the impact of employee job rotation on the performance of PT HK Realtindo employees. This method of research is qualitative research, with primary data and carried out using an interviews process. The data is analyzed through data reduction process, then data is presented, and finally drawing conclusions or verification. The results of this study show tha the implementation of work rotation at PT HK Realtindo is generally going quite well with employees allocated on target. To support the implementation of job rotation, the company provides facilities in the form of self-development in the form of mentoring and training, and other aspects such as salaries and benefits. This support makes employees performance, so that it is easy to achieved organizational goals. This rotation program has a positive impact in achieving organizational goals, by showing employee involvement in the organization, and being able to achieve the performance targets given by the company.